Uncovering of cytochrome P450 anatomy by SecStrAnnotator - Midlik, Adam; Navrátilová, Veronika; Moturu, Taraka Ramji; Koča, Jaroslav; Svobodová, Radka; Berka, Karel (Scientific reports, 2021)
Protein structural families are groups of homologous proteins defined by the organization of secondary structure elements (SSEs). Nowadays, many families contain vast numbers of structures, and the SSEs can help to orient within them. Communities around specific protein families have even developed specialized SSE annotations, always assigning the same name to the equivalent SSEs in homologous proteins. A detailed analysis of the groups of equivalent SSEs provides an overview of the studied family and enriches the analysis of any particular protein at hand. We developed a workflow for the analysis of the secondary structure anatomy of a protein family. We applied this analysis to the model family of cytochromes P450 (CYPs)-a family of important biotransformation enzymes with a community-wide used SSE annotation. We report the occurrence, typical length and amino acid sequence for the equivalent SSE groups, the conservation/variability of these properties and relationship to the substrate recognition sites. We also suggest a generic residue numbering scheme for the CYP family. Comparing the bacterial and eukaryotic part of the family highlights the significant differences and reveals a well-known anomalous group of bacterial CYPs with some typically eukaryotic features. Our workflow for SSE annotation for CYP and other families can be freely used at address https://sestra.ncbr.muni.cz .
Keywords: Software; sekvenční analýza proteinů; Molecular Dynamics Simulation; software; simulace molekulární dynamiky; systém (enzymů) cytochromů P-450; Animals; lidé; Cytochrome P-450 Enzyme System; Humans; Sequence Analysis, Protein; zvířata